WHERE DOES EVIL RESIDE? A COMPARATIVE STUDY OF HANNAH ARENDT AND ANTJIE KROG (The Pretoria Student Law Review, 2021)
Two significant twentieth century female philosophers, Hannah Arendt and Antjie Krog, critically evaluated two of the most egregious humanitarian crimes of the past hundred years. In the essay ‘Personal responsibility under dictatorship’, Arendt (1906-1975) used the trial of Adolf Eichmann, who was convicted and executed for crimes against humanity committed during World War II, to explain the connection between existence and thought and the necessity of a commitment to thinking; it was also a mouthpiece to voice her opinion on judgment, punishment, vengeance, collective responsibility and morality. In her book Country of my skull2 Krog (1952- ) reported on and analyzed the history, process and effects of the Truth and Reconciliation Commission (‘the TRC’), a commission established to assist the new democratic South Africa in dealing with Apartheid crimes.
Keywords: female philosophers; Hannah Arendt; Antjie Krog; egregious humanitarian crimes; ‘Personal responsibility under dictatorship’